Educazione in età adulta Ricerche, politiche, luoghi e professioni - Federighi, Paolo (Studies on Adult Learning and Education, 2018)
This volume shows the outcome of a series of meetings and seminars which, on several levels, contributed to the construction of the International Conference La ricerca sull'Educazione in età Adulta nelle università italiane held at the University of Florence on the 23rd and 24th November 2017. The different contributions have tried to answer the question on the origin and development of adult education in Italy within academic contexts. What does it mean to work in this research field? The interviewed directors have reflected on a number of research approaches and have reconstructed the variety of theories, models and authors which outlined the development of this discipline in Italy over the last fifty years. Among the covered topics are: increasing the educational quality of the workplace, understanding the education incorporated in the workplace, studying the aims of education in formal and informal contexts. This has led to a new and original theme, which had however not been touched by the Italian academic literature, namely the question of inequalities and relative poverty, two important phenomena for understanding the development of future societies.